Ação afirmativa e cotas: um percurso pela imprensa brasileira (de 1995 a 2002) - Santos, Ana Elisa de Carli dos (2005)
The racial question acquired centrality in the Brazilian context lately, due to mobilization arond the offer about especific public politics towards to black people, or affirmative action . This theme is fundamental because propose one reorientation in the sense of the socials relations with basis the race and colour. In this context, the press mass media has been one important sphere of boarding about the topic of the affirmative action. The captivation of the perceptions and representations furnished by national writting printing press constitute fountain of investigation of this search. The techniques of the content analysis and framing analysis has been used to capture the types of orientation that structure the news. The theme is bras in the mass media and this space of discussion supply one ample possibility of negotiation and political and social legitimacy of the interests of black people in Brazil.